Social polarization: towards the text mining study - Roman Kyrychenko (Соціологічні студії, 2022)
This article suggests a way to concretize the concept of social polarization, which will be most suitable for a) empirical operationalization; b) a complete description of existing social conflicts; c) will be consistent with existing sociological theories. The implementation of this task opens the way to studying this phenomenon through the method of text mining. We see two main problems with the concept of social polarization in sociology: (1) Social polarization is used as a beautiful metaphor to describe contemporary political situations, not as a strong operationalized concept. The concept must create vast opportunities to study social reality, interpret more processes; (2) The mathematic interpretation of social polarization is conducted on somewhat idealized distributions; there is a lack of real empirical data verification. These two problems also create one big problem: mathematical conceptualization of social polarization and empirical studies of social polarization are unrelated. We propose a way to solve this problem through the construction of our social polarization theoretical framework. The way that allowed us to do this was in the concretization of social polarization and its connection with sociological theories of conflict. The article’s key idea is to show that this concept is suitable for operationalization for two reasons: its ability to describe the causes and nature of social conflicts and its measurability.